2015
DOI: 10.1016/j.eatbeh.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Two facets of stress and indirect effects on child diet through emotion-driven eating

Abstract: Objective Stress has been associated with high-calorie, low-nutrient food intake (HCLN) and emotion-driven eating (EDE). However, effects on healthy food intake remain unknown. This study examined two facets of stress (self-efficacy, perceived helplessness) and food consumption, mediated by EDE. Methods Cross-sectional data from fourth-graders (n = 978; 52% female, 28% Hispanic) in an obesity intervention used self-report to assess self-efficacy, helplessness, EDE, fruit/vegetable (FV) intake, and high-calor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
1
21
0
2
Order By: Relevance
“…An experimental study among 43 US children aged 5–9 y of age found that greater stress-related cortisol was related to greater energy intake in the absence of hunger among the 8–9 year olds, although not in the younger children [ 26 ]. Finally, another US study showed that high stress self-efficacy (i.e., ability to handle stress) among fourth-graders was related to higher fruit and vegetable intake [ 27 ]. In summation, it is possible that the associations we observed between externalizing behavior and diet could be related to stress and emotional eating.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study among 43 US children aged 5–9 y of age found that greater stress-related cortisol was related to greater energy intake in the absence of hunger among the 8–9 year olds, although not in the younger children [ 26 ]. Finally, another US study showed that high stress self-efficacy (i.e., ability to handle stress) among fourth-graders was related to higher fruit and vegetable intake [ 27 ]. In summation, it is possible that the associations we observed between externalizing behavior and diet could be related to stress and emotional eating.…”
Section: Discussionmentioning
confidence: 99%
“…Os fatores que contribuem para essa causa são: os internos que são os genéticos no qual os indivíduos tornam susceptíveis ao ganho de peso se entrarem em contato com fatores do meio que sejam favoráveis a isso; e os metabólicos que se referem ao gasto energético, ou seja, à energia gasta pelo organismo para realizar todo tipo de atividade. Outros fatores que contribuem são os externos como os Alimentares que depende do tipo de alimentos, a forma de preparo e as preferências alimentares; os psicológicos que são os problemas emocionais e os psicológicos que podem levar a criança a comer mais como mecanismo de compensação ou de defesa; e as atividades físicas onde o estilo de vida da criança reflete um fator muito importante no desenvolvimento da obesidade (BAR-BOSA, 2008;HUGHES et al, 2015;TATE et al, 2015). De acordo com estudos realizados, a obesidade pode ser dividida em obesidade de origem exógena -a mais frequente -e endógena.…”
Section: Introductionunclassified
“…22,32 Impacting both physical and psychological wellbeing one mechanism of obesity development that has not been well explored is that due to excess caloric intake as a result of being addicted to foods with high fat and sugar content as discussed by Merlo et al 22 In addition, data from animal models does suggest that the food addiction hypothesis in relation to obesity is potentially relevant. 33 Other evidence does suggest that in addition to a possible increased preference for sweetness, 22 contributing to this association may be various forms of stress, that have been correlated with emotion-driven eating, of high calorie and low nutrient food intake 34 and the specific manufacture of obesogenic foods that fosters addiction. 29 It also seems noteworthy that obesity is more evident among the poorer classes who eat more foods in general that could be termed hyperpalatable, but low in nutrient value.…”
Section: Discussionmentioning
confidence: 99%